APPLICATION OF THE MULTIVARIATE ADAPTIVE REGRESSION SPLINE (MARS) METHOD IN ANALYZING MISCLASSIFICATION OF ELEMENTARY SCHOOL ACCREDITATION DATA IN THE CITY OF TEBING TINGGI - Puteri Fajar Addini; Wira Hadi; Pria Muslim Rasmanna Harahap (Sean Institute, 2023)
Education is always side by side in life and inseparable for every soul that continues to grow and develop. The quality of education in Indonesia can be seen from accreditation, certification, and education quality assurance. The government conducts accreditation to assess the feasibility of educational programs or units. The classification accuracy of school accreditation assessment is a very interesting topic to study using the classification method. The method to be used in this research is the Multivariate Adaptive Regression Spline (Mars) method for model building. Testing the significance of the model using the F test statistic and testing the model parameters (individual test) using the T test statistic and evaluation of the classification procedure. The purpose of this research is to analyze the misclassification of accreditation data and test the resulting MARS model which is very good at classifying elementary schools in Tebing Tinggi City based on the accreditation rating obtained.